Pengaruh Permainan Tradisional Terhadap Peningkatan Kebugaran Jasmani Pada Siswa SMPN 3 Bondowoso - Dimas Bagus Yulianto; Gatot Margisal Utomo (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2024)
The purpose of this study was to determine the effect of traditional games on increasing physical fitness in students of SMPN 3 Bondowoso. The population in this study were students of SMPN 3 Bondowoso, totaling 38 students. The researcher planned to take a sample of 20 students of SMPN 3 Bondowoso. To determine from population to sample using random sampling technique (random / lottery). This type of research is quantitative research using quasi-experimental design. While the design or design in this study used the Non-Randomize Control Group Pretest-Posttest. The results of the analysis found that the value of sig. (2-tailed) in the experimental group is 0.009, in the control group is 0.053, so the value of sig. (2-tailed) in the experimental group > 0.05, it can be stated that traditional games have an effect on increasing physical fitness in students of SMPN 3 Bondowoso. So that the research entitled the effect of traditional games on increasing physical fitness in SMPN 3 Bondowoso students can be used as PJOK teachers to serve as a reference or guide in providing training programs or materials in particular to improve physical fitness because traditional games have been proven to improve physical fitness in SMPN students 3 Bondowoso. Keywords: traditional games, physical fitness